PENGEMBANGAN E-MODUL KIMIA BERBASIS KEMAMPUAN BERPIKIR KREATIF DENGAN MENGGUNAKAN KVISOFT FLIPBOOK MAKER - Cici Romayanti; Agus Sundaryono; Dewi Handayani (ALOTROP, 2020)
The aim of this research is to determining level of feasibility and response of students from the development of e-modules in chemistry course based on creative thinking ability using the Kvisoft Flipbook Maker on material electrolyte and non-electrolyte solution in SMA Negeri 9 Kota Bengkulu. The type of research used is R & D (Research & Development), which uses the ADDIE development model (analysis, design, development, implementation, evaluation) with the limitation of stage until implementation. The results of this research show that the chemistry-based E-Module based on creative very feasible and feasible to use with the validation results from media experts was 97.7%, material expert validation was 90.2%, readability the small group trials conducted by 9 students in class X MIPA 2 was 97.04% and student responses in the large group trial conducted by 25 students in class X MIPA 1 was 86.4% (very feasible category). This shows that e-modules in chemistry course based on the ability to think creatively by using the kvisoft flipbook maker are very suitable to be used in the learning process